The Influence of Leaf Harvesting Methods on Tobacco Seed Production and Quality - Parnidi Parnidi; Imam Santoso; Mochamad Sohri; Dian Hariyanto; Anik Herwati (Jurnal Penelitian Pendidikan IPA, 2023)
To produce high-quality seeds, the harvest must be carried out on time so that the seed maturity is almost uniform. Like wise to produce seeds of high physiological quality. The study was conducted at the Karangploso Experimental Garden, Balittas Malang, in January-October 2017. The varieties used were Prancak-N1, with 6 treatments namely: (1) Leaves harvested and shredded, (2) Leaves harvested and shredded are not discarded, (3) Leaves not harvested and suckers not removed (4) Leaves not harvested and shredded (5 koseran leaves not harvested shingles disposed and (6) Koseran leaves harvested and shredded discarded.The treatment was planted as many as 10 polybags with a size of 20 kg of soil, one plant per polybag, population of each treatment as many as 10 plants with 3 replications. The fertilizer used was NPK fertilizer with a dose of 15 grams per plant. Analysis used Randomized Group Design repeated 3 times, to calculate the variance using the Duncan Distance Test (DMRT) with a level of 5%. The purpose of the study was to determine the effect of the treatment of harvesting leaves and tobacco flowers on the production and quality of the seeds produced. The results showed that the highest seed production from the six treatments was treated with leaves not harvested and shredded, the highest production of seeds reached 17.4 grams, but not significantly different from the treatment of koseran leaves not the harvested sirung was disposed of (16.10 grams) and the coseran leaves were harvested, the flush was disposed of (15.70 grams). For the highest seed vigor test, the leaves were not harvested and the flush was disposed (17.40%), while the highest germination test for the flush treatment was reached (93.33%), but not significantly different from the treatment of the leaf leaves not harvested by sirung discarded (91.33%) and the treatment of koseran leaves was harvested, flush was disposed (84.68%). Observation of abnormal sprouts from the six treatments was not significantly different between 1.33%-2.33%